The Influence of Ethnolinguistic Background on the Code-Mixing Patterns of Islamic Boarding School Students at Al-Hidayah Modern Islamic Boarding School, Jambi - Jingga Natasya; Sulhi M Daud; Rofiazka Fahmi Huda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the influence of ethnolinguistic background on the code-mixing patterns of students and to identify the factors that encourage code mixing among students at Al-Hidayah Modern Islamic Boarding School, Jambi. This research is motivated by the phenomenon of using Arabic and English as the official languages in the boarding school, while in daily practice students frequently combine them with Indonesian and regional languages. The diversity of students' regional origins, mother tongues, and cultural backgrounds is assumed to influence their language use in everyday communication. This study employed a descriptive qualitative approach. Data were collected through observations of students' interactions in various daily activities within the boarding school and analyzed descriptively to identify the forms of code mixing and the factors underlying their occurrence. The findings indicate that ethnolinguistic background plays an important role in shaping students' code-mixing patterns involving Arabic, English, Indonesian, and regional languages. Code mixing occurs due to the influence of students' mother tongues, language habits prior to entering the boarding school, social identity, communication convenience, and the multilingual environment of the institution. The study concludes that ethnolinguistic background is closely associated with students' code-mixing practices and constitutes an important factor in shaping communication patterns at Al-Hidayah Modern Islamic Boarding School, Jambi.